Strengthening Islamic Sharia Through Effective Communication Strategies: A Case Study of UIN Ar-raniry Banda Aceh - Ibnu Sa’dan; Syukur Kholil; Hasrat Efendi Samosir (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2025)
This research aims to analyze the effective communication strategies at State Islamic University (UIN) Ar-Raniry to strengthen the understanding and application of Islamic Sharia, given the institution's critical role in Aceh. Employing a qualitative case study method through interviews, observations, and document analysis of eight research subjects (R1–R8), the findings indicate that UIN Ar-Raniry implements a comprehensive strategy combining traditional approaches such as interpersonal communication, student mentoring programs, and collaboration with scholars with the utilization of digital media (social media, websites) to reach a wider audience. These strategies involve contextual messaging and interactive discussions, as well as the integration of Sharia values into the curriculum and the development of Islamic character. The success of these strategies is evidenced by an increased understanding of Sharia values among students, high participation in religious activities, and the application of Islamic ethics in academic life. Academically, these findings contribute by affirming the importance of synergy between modern and traditional communication and collaboration among stakeholders to support the optimal implementation of Islamic Sharia.